Predictors of Acute Chemotherapy-Associated Toxicity in Patients with Ewing Sarcoma - Sharib, Jeremy M. (2011)
BACKGROUND: Ewing sarcoma (ES) is a malignant tumor of bone and soft tissue of children and young adults. Patients with ES are treated with intensive chemotherapy regimens. We describe predictors of acute chemotherapy-associated toxicity in this population. PROCEDURE: In this retrospective cohort study, records of ES patients treated at two academic medical centers between 1980 and 2010 were reviewed. Grade 3 and 4 non-hematologic chemotherapy-associated toxicities during frontline therapy were recorded for each patient, along with potential clinical and demographic predictors of toxicity. Bivariate analyses were performed using the Fisher exact test. Multivariate analysis was performed using logistic regression. RESULTS: The cohort included 142 patients with ES and toxicity data. In bivariate analyses, age <12 years at diagnosis, Latino ethnicity, low family income, and treatment on a clinical trial were associated with higher incidence of toxicity (p <0.01). Tumor size, site, stage, mode of local control, body mass index, overall chemotherapy exposure and dose-intensity were not associated with toxicity. In multivariate analysis, low income (odds ratio (OR) 4.97, 95% CI 1.9–13.1), clinical trial enrollment (OR 3.67, 95% CI 1.2–10.9), pelvic tumor site (OR 3.88, 95% CI 1.17–12.88), and age <12 years (OR 2.8, 95% CI 1.0–7.5) were independent predictors of toxicity. CONCLUSION: ES patients who are younger, of Latino ethnicity, have pelvic tumors or low income have higher rates of toxicity that may require increased supportive care. Treatment on a clinical trial was also associated with higher rates of toxicity, though this finding may reflect better reporting in these patients.